15.9k views
4 votes
I need to solve for X but I have no idea how to do this

I need to solve for X but I have no idea how to do this-example-1
User Glenn N
by
5.3k points

2 Answers

5 votes
x = 6

EF + FG = -5+3x, which can be written as:
-5 + 3x - 9 = x-2
+ 2 +2
-3x -3x
-12 = -2x
Divide both sides by (-2)
x = 6

[check: 9 + (6)-2 = -5+3(6) -> 13 = 13; true]
User Muneem Habib
by
5.4k points
5 votes

Answer:

EG = EF + FG


{ \tt{ (- 5 + 3x) = 9 + (x - 2)}} \\ \\ { \tt{3x - x = 9 - 2 + 5}} \\ \\ { \tt{2x = 12}} \\ \\ { \tt{x = 6}}

User Gunnerone
by
5.0k points